Evidence-Based Recommendations for Effective Enrichment to Improve the Welfare of Caged Hens Used for Research and Teaching Purposes - Amy F. Moss; Rebel Northey; Sukirno; Aamir Nawab; Nasima Akter; Peta S. Taylor; Hiep Thi Dao (Poultry)
Currently, there are no guidelines on housing or recommendations for practical environmental enrichments for chickens used for research and teaching purposes. This study was conducted to identify optimal enrichment programs to improve the health and welfare of caged hens used for teaching and research purposes. The 24-week-old Hy-line Brown laying hens (n = 168) were allocated at random to six enrichment programs/treatments with 14 replicate cages of two birds per cage during a 5-week experiment. Hens had physical access to the following treatments: no enrichment provided (control); round, wooden perches provided (perch); scratch pads made of wood and covered with sandpaper provided (scratch pad); hanging CDs provided (hanging CD); all three enrichment forms provided (complex environment); and each enrichment form provided on a 2-week rotation (novelty). While the egg quality was consistent, the complex group had a significantly lower feed intake (p < 0.001) but similar egg mass; thus, they also had a lower feed conversion ratio (p < 0.001). Additionally, hens in the complex treatment group had the leanest average body weight at week 5 (p < 0.01). It should be noted that while some measures of welfare did show significant differences, the biological or practical difference may be negligible, as in the case of the body condition score in this study. The results show that providing three different forms of environmental enrichment had positive effects on the welfare, health condition, and laying performance of laying hens relative to no enrichment or only one enrichment item.